STRATEGIC PRIORITIES FOR NATIONAL DEVELOPMENT. IMPROVING THE SOCIO-ECONOMIC EFFECTIVENESS OF UZBEKISTAN’S INVESTMENT POLICY - SHARIPOVA , GUZAL; ODILOVA , MUSLIMA (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
At this stage of large-scale economic transformation in the Republic of Uzbekistan, investment policy is ceasing to be merely a tool for capital accumulation and is becoming a key driver of far-reaching structural reforms. In the current period, we are witnessing a qualitative transition from the stage of macroeconomic stabilisation to a strategy of active, comprehensive investment, where the main value lies not only in the volume of funds attracted, but also in their real impact on the standard of living of every citizen. In this context, the relevance of this topic stems from the need to seek new sources of sustainable growth amid global uncertainty and a shortage of financial resources.